Ammonium polyphosphate modified with β-cyclodextrin crosslinking rigid polyurethane foam: Enhancing thermal stability and suppressing flame spread - Li, Qimin; Wang, Jingyu; Chen, Lamei; Shi, Hui; Hao, Jianwei (Polymer degradation and stability, 2019)
Ammonium polyphosphate modified with β-Cyclodextrin (β-CD) as intumescent flame retardants was prepared and then incorporated in rigid polyurethane foam (RPUF) to improve thermal stability and flame retardancy. Scanning electron microscope (SEM), Transmission electron microscope (TEM), Fourier-transform infrared (FTIR) spectra and X-ray photoelectron spectroscopy (XPS) were used to characterize the modified APP (β-APP). The results showed that the surface of β-APP was covered of β-CD and the dispersibility of β-APP in substrate was improved apparently. In addition, the influence of β-APP on the cell structure, crosslink density, thermal stability and flame retardancy of RPUF were investigated. The results showed that β-APP was able to promote cellular distribution of RPUF into smaller and homogeneous. The results of dynamic thermomechanical analysis (DMA) and thermogravimetric analysis (TGA) indicated that the glass transition temperature (Tg) and crosslink density of β-APP/RPUF increased obviously, and the thermal stability of β-APP/RPUF was better than other FR-RPUFs. During combustion, flame spreading speed of 25 wt%β-APP/RPUF reduced by 67.3% relative to pure RPUF and extinguish time decreased to 2.1s with the most complete inner char and the most dense outside char. In addtion, peak heat release rate (PHRR) of the sample decreased by 43.8% compared to pure RPUF. Therefore β-APP exhibited a prominent charring property and flame-retardant effect in condensed phase for RPUF. •Rigid polyurethane foams (RPUF) have several excellent performance, including thermal insulation, waterproof, light weight, resisting pressure and charring while burning, because of its low thermal conductivity (0.018–0.028W m-1 K-1), high obturator rate, low density, high compressive strength and no-dropping [1–4]. Therefore, RPUF have been widely applied in some heat preservation fields relating to energy-saving, such as construction, pipeline and refrigeration. However, the limiting oxygen index of RPUF is as low as 17–20%, which means that RPUF is easy to be ignited.•Ammonium polyphosphate (APP) is able to provide enough acid source for RPUF to product inorganic acid as dehydrating agent but without enough carbon source and good compatibility. Therefore, searching for suitable carbon agents and improving distribution of APP in RPUF is very necessary. β-Cyclodextrin (β-CD) is a bio-based product and “green” carbon agent that is linked by more than six glucose. On the one hand, this structural feature of containing many carbon rings and hydroxyl groups enabled β-CD to provide carbon source in IFR systems validly. On the other hand, the hydroxyl is able to reactive with isocyanate so as to improve the crosslink density of RPUF.•In this study, the surface modified APP by using β-CD as a intumescent flame retardants is covered by ring carbon chain and hydroxy groups to enhance crosslink density and improve fame retardance for RPUF. Based on characterization of the modified APP (β-APP), the cell morphology and crosslink density, the thermal stability and flame retardance of RPUF added β-APP were studied, and the results will be helpful for designing a new intumescent RPUF system.